2017
DOI: 10.1016/j.redox.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear actions of physiological agents: Finite disarrangements elicit fitness benefits

Abstract: Finite disarrangements of important (vital) physiological agents and nutrients can induce plethora of beneficial effects, exceeding mere attenuation of the specific stress. Such response to disrupted homeostasis appears to be universally conserved among species. The underlying mechanism of improved fitness and longevity, when physiological agents act outside their normal range is similar to hormesis, a phenomenon whereby toxins elicit beneficial effects at low doses. Due to similarity with such non-linear resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 153 publications
(213 reference statements)
0
4
0
Order By: Relevance
“…The phenomenon by which an agent is stimulatory (then potentially beneficial) at low doses and hazardous at higher doses is known as "hormesis" or "adaptive response." Hormesis was shown to occur at all levels of the biological organization (cell, tissue or the whole body), for a variety of effects, both acute or long-lasting (including carcinogenesis), as well as in relation to physiological agents (see for instance [40][41][42]). The adaptive response may result in increased resilience of tissues and the whole body to environmental and physiological stresses.…”
Section: Iramentioning
confidence: 99%
“…The phenomenon by which an agent is stimulatory (then potentially beneficial) at low doses and hazardous at higher doses is known as "hormesis" or "adaptive response." Hormesis was shown to occur at all levels of the biological organization (cell, tissue or the whole body), for a variety of effects, both acute or long-lasting (including carcinogenesis), as well as in relation to physiological agents (see for instance [40][41][42]). The adaptive response may result in increased resilience of tissues and the whole body to environmental and physiological stresses.…”
Section: Iramentioning
confidence: 99%
“…According to findings, H2O2 below 100 µM is nontoxic. Previous studies have demonstrated that H2O2 can inhibit cell growth and cause cell death; higher doses of H2O2 can lead to oxidative stress (24). In this study, 100 µM H2O2 induced oxidative stress with less severe apoptotic effects.…”
Section: Discussionmentioning
confidence: 47%
“…11,39 Such dichotomy in the effects of UPRmt elements on heart could be a result of a non-linear response, whereby a moderate activation of UPRmt protects cardiomyocytes, while its excessive activity becomes harmful. 1,40 UPRmt protease YME1L reduces mitochondrial protein import by inactivating TIM17A, which is a mechanism downstream of eIF2α activation. 8 Our results demonstrate downregulation of most of tested elements of TIM23 and TIM22 translocons in ICM and DCM, which could in patients with HF prevent overload of mitochondria with proteins in a situation when UPRmt activity is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, upregulation of LONP1 and OMI caused HF 11,39 . Such dichotomy in the effects of UPRmt elements on heart could be a result of a non‐linear response, whereby a moderate activation of UPRmt protects cardiomyocytes, while its excessive activity becomes harmful 1,40 …”
Section: Discussionmentioning
confidence: 99%